2020
DOI: 10.46624/bjmhr.2020.v7.i1.001
|View full text |Cite
|
Sign up to set email alerts
|

actors Associated with Substance Abuse by Students in Medical Training Colleges in South Nyanza Region, Kenya

Abstract: Substance abuse is a worldwide public health challenge with college youth being among those affected. An estimated 10-15 % of students in medical training institutions risk substance abuse in their lifetime as they are not immune to the predisposing factors associated with the abuse. The conduct and efficiency of medical training college (MTC) students as future healthcare professionals may be impacted negatively by substance abuse; consequently, the patients are at risk. In Kenya, substance abuse is prevalent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 16 publications
1
13
2
Order By: Relevance
“…Other topics explored:In addition to prevalence and associated factors, these studies explored other topics including agreement between self-reported alcohol use and the biomarker phosphatidyl ethanol ( 92), primary health care workers self-e cacy for SUD management ( 93), reasons for substance use (27,30,94,95), and tobacco quit intentions(96). Papas et al (92) reported a lack of agreement between self-reported alcohol use and the biomarker phosphatidyl ethanol among PLHIV with AUD.…”
Section: Studies Qualitatively Exploring Various Themes On Substance Use/sud (But Not Assessing Interventions)mentioning
confidence: 99%
See 2 more Smart Citations
“…Other topics explored:In addition to prevalence and associated factors, these studies explored other topics including agreement between self-reported alcohol use and the biomarker phosphatidyl ethanol ( 92), primary health care workers self-e cacy for SUD management ( 93), reasons for substance use (27,30,94,95), and tobacco quit intentions(96). Papas et al (92) reported a lack of agreement between self-reported alcohol use and the biomarker phosphatidyl ethanol among PLHIV with AUD.…”
Section: Studies Qualitatively Exploring Various Themes On Substance Use/sud (But Not Assessing Interventions)mentioning
confidence: 99%
“…In that study, higher self-e cacy correlated with a higher proportion of patients with AUD in one's setting, access to mental health worker support, HCW's cannabis use at a moderate risk level, and belief that AUD is manageable in outpatient settings. Common reasons for substance use included leisure, stress and peer pressure among psychiatric in-patients ( 30), curiosity, fun, and peer in uence among college students (94); peer in uence, idleness, easy access, and curiosity among adults in the community (27); and peer pressure, to get drunk, to feel better and to feel warm among street children (95). Atwoli et al 2011 (97) reported that most students were introduced to substances by friends while Astrom et al 2004 (98) reported that HCWs, parents and school teachers were not discussing tobacco harms with youth.…”
Section: Studies Qualitatively Exploring Various Themes On Substance Use/sud (But Not Assessing Interventions)mentioning
confidence: 99%
See 1 more Smart Citation
“…The highest prevalence rate for the use of prescription medication was reported as 21.2% among PWID [190]. One study each reported on the prevalence of emerging drugs [122] and ecstasy [153]. The studies were both conducted among adolescents and youth.…”
Section: Plos Onementioning
confidence: 99%
“…Five studies investigated the reasons for substance use. Common reasons for substance use included leisure, stress and peer pressure among psychiatric patients[28], curiosity, fun, and peer influence among college students [123], peer influence, idleness, easy access, and curiosity among adults in the community [25], and peer pressure, to get drunk, to feel better and to feel warm among street children [74]. Atwoli et al 2011 [72] reported that most students were introduced to substances by friends.…”
Section: Plos Onementioning
confidence: 99%